Phosphate Solubilizing Bacteria Adaptive to Vinasse - Kahar Muzakhar; Sutoyo; Ahmad Bukhari Saragih (Journal of Mathematical and Fundamental Sciences, 2015)
Microorganisms identified as phosphate solubilizing bacteria (PSB) adaptive to vinasse were successfully screened from sugarcane soil from an agriculatural estate in Jatiroto. By conducting a screening on Pikovskaya’s agar medium (PAM), we found that five different isolates were detected as PSB (pvk-5a, pvk-5b, pvk-6b, pvk-7a, and pvk-8a). Of the five isolates only three could be grown and were found to be adaptive to vinasse based medium without any nutrients added (pvk-5a, pvk-5b and pvk-7a). The three isolates were characterized as coccus and Gram negative with no endospores detected. We suggest that these three isolates can be used as biofertilizer agent to support organic farming.